Targeting the heparin-binding domain of fibroblast growth factor receptor 1 as a potential cancer therapy - Ling, Ling (Mol Cancer, 2015)
BACKGROUND: Aberrant activation of fibroblast growth factor receptors (FGFRs) deregulates cell proliferation and promotes cell survival, and may predispose to tumorigenesis. Therefore, selective inactivation of FGFRs is an important strategy for cancer therapy. Here as a proof-of-concept study, we developed a FGFR1 neutralizing antisera, IMB-R1, employing a novel strategy aimed at preventing the access of essential heparan sulfate (HS) co-receptors to the heparin-binding domain on FGFR1. METHODS: The mRNA and protein expression level of FGFR1 and other FGFRs were examined in several lines of breast cancer and osteosarcoma cells and corresponding normal cells using Taqman real-time quantitative PCR and Western blot analysis. The specificity of IMB-R1 against FGFR1 was assessed with various ELISA-based approaches and Receptor Tyrosine Kinase array. Proliferation assay and apoptosis analysis were performed to assess the effect of IMB-R1 on cancer cell growth and apoptosis, respectively, in comparison with known FGFR1 inhibitors. The IMB-R1 induced alteration of intracellular signaling and gene expression were analysed using Western blot and microarray approaches. Immunohistochemical staining of FGFR1 using IMB-R1 were carried out in different cancer tissues from clinical patients. Throughout the study, statistical differences were determined by Student’s t test where appropriate and reported when a p value was less than 0.05. RESULTS: We demonstrate that IMB-R1 is minimally cross-reactive for other FGFRs, and that it potently and specifically inhibits binding of heparin to FGFR1. Furthermore, IMB-R1 blocks the interaction of FGF2 with FGFR1, the kinase activity of FGFR1 and activation of intracellular FGFR signaling. Cancer cells treated with IMB-R1 displayed impaired FGF2 signaling, were unable to grow and instead underwent apoptosis. IMB-R1-induced cell death correlated with a disruption of antioxidative defense networks and increased expression of several tumor suppressors and apoptotic proteins, including p53. Immunostaining with IMB-R1 was stronger in human cancer tissues in which the FGFR1 gene is amplified. CONCLUSION: Our study suggests that blocking HS interaction with the heparin-binding domains of FGFR1 inhibited cancer cell growth, which can be an attractive strategy to inactivate cancer-related heparin-binding proteins. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12943-015-0391-4) contains supplementary material, which is available to authorized users.